PENGARUH DPR, EPS DAN DER TERHADAP HARGA SAHAM - Rahmawati, Dwi; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis study is meant to identify and to analyze the influence of dividend payout ratio, earnings per share, debt to equity ratio to the stock price of Property and Real Estate companies which are listed on the Indonesia Stock Exchange (BEI).The population has been obtained by using purposive sampling method on Property and Real Estate companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods and based on the predetermined criteria 37 Property and Real Estate companies have been obtained as samples. The analysis method has been done by using multiple linear regression analysis and the SPSS 23 (Statistical Product and Service Solutions).The result of hypothesis testwhich has been done by using t test shows that all research variables i.e. dividend payout ratio, earnings per share and debt to equity ratio give significant and positive influence to the Property and Real Estate companiesKeywords: Dividend payout ratio, earning per share, debt to equity ratio, stock price